The Economic Empowerment of Women Micro Entrepreneurs: How is the Islamic Wealth Management Impact? - Nurasyiah, Aas; Monoarfa, Hilda; Kusnendi, Kusnendi; Firmansyah, Firmansyah; Rosida, Rida; Ismail, Shafinar (Review of Islamic Economics and Finance, 2023)
Purpose – This research aims to analyze what factors keep women economically empowered during the COVID-19 period. The basic theory used is the theory of famines of poverty (Amartya Sen), which states that one of the main factors for women's economic empowerment is access to financial resources. In this study, the financial governance carried out refers to the Islamic Wealth Management concept developed by experts.Methodology - The method used in this study is quantitative with a causality approach, and besides that, the data analysis technique used is Structural Equation Modeling-Partial Least Square (SEM-PLS). The subjects of this study were female micro-entrepreneurs who were able to be empowered during the Covid-19 pandemic. Findings - The results of this study conclude that of the five aspects of Islamic Wealth Management, there are wealth accumulation, wealth protection, and wealth distribution have a significant effect on women's economic empowerment. Furthermore, the wealth creation and wealth purification variables do not have a significant effect on women's economic empowerment.